New algorithm for the diagnosis of hereditary dystonia - Camargos,Sarah (2012)
Taking into account the crescent interest in the field of dystonia genetics, we have organized a didactic and fast algorithm to diagnose the main forms of hereditary dystonias. The key branch of this algorithm is pointed to dystonia classification in primary, plus, or paroxysmal. The specific characteristics of each syndrome will reveal the diagnosis.